Death and Evanescence in the Book of Ecclesiastes. An Interpretation of Eccl 2:13–17 and 3:16–22 - Peetz, Melanie (Revista de Cultura Teológica, 2020)
The Book of Ecclesiastes talks about human death and evanescence candidly and powerfully—more so than almost any other book in the Bible. Qoheleth (Greek Ecclesiastes), a wisdom teacher and the central character in this book, takes death seriously. For him, it represents the ultimate boundary to human life, although he does not claim that there is nothing after it. Still, for him, death is as unavoidable as it is final. Therefore, he argues to treat life as a one-time opportunity, accept life's goods as a gift from God, and enjoy them.